Soft denture liner and its additives (A review of literature) - Ibrahim Ali Al-Najati; Ghasak Husham Jani ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Soft liners are used with patients who cannot tolerate the hard acrylic base. It is used in complete and partial removable dentures to distribute functional loads homogeneously on the denture-bearing tissues to increase patient acceptance and relieve pain. These materials are recommended in cases of irregular bone resorption, bony undercuts, thin atrophic mucosa, immediate prosthesis, healing after implant placement, and for patients with bruxism and xerostomia.However, the structure of the soft liner encourages the colonization of microorganisms, so the soft liner must be modified to overcome any possible infection that may occur during use, especially to prevent denture stomatitis, the most common disease associated with denture wearing caused by candida albicans.